Users’ Preferences Of Usability Of Urban Parks In Tabriz, Iran - Hami, Ahmad (2009)

(untitled)
Nowadays, urban parks are considered one of the most important and essential parts of urban fabrics. Parks introduce multiple opportunities for users including, active and passive recreation, social communication, and conservation of nature environments. It is important that parks design meets residents’ needs and demands. In many cases, urban parks are designed based on designers’ insights and knowledge, and most of the time the design doesn’t meet the users’ needs; the ultimate result being low, or no, use of urban parks. Urban parks in Tabriz, Iran, experience this problem probably due to wrong speculation of users’ motivation for park use and preferred activities there in. This research aims at understanding users’ motivations behind visiting parks and their preferred activities in urban parks at Tabriz, Iran. A survey study was deemed appropriate for answering the research questions and meeting its objectives. The survey instrument was designed to have both open and close-ended questions about how people go to parks, motives for visiting parks, and their preferred park’s activities. The survey questionnaire was conducted via randomly sampling method among 208 of the parks’ users in Tabriz.Two local parks; El Goli and Big Park, were selected for this study. The results indicate that nature in the park is the most important motive for people to visit the parks in Tabriz. Socialization with family and passive recreation were found to be the most preferred visitor activities. In addition, the participants highlighted that safety of El Goli Park’s environment and maintenance of Big Park need to be improved. This research unfolds user’s insights and opinions about pattern, orientation, and tendencies of park use in Tabriz. It is highly recommended that future research be conducted to explore other segment of society such as teenagers’ motives and preferences for park activities and visitation. It is also essential that the future designs of parks in Tabriz put the findings of this study into practice.